NMR‐based metabolomics and bioassays to study phytotoxic extracts and putative phytotoxins from Mediterranean plant species. Issue 5 (20th June 2019) - Scognamiglio, Monica; Graziani, Vittoria; Tsafantakis, Nikolaos; Esposito, Assunta; Fiorentino, Antonio; D'Abrosca, Brigida; Lanzotti, Virginia; Grauso, Laura
Abstract: Introduction: Mediterranean plants are characterised by a high content of bioactive secondary metabolites that play important roles in plant–plant interactions as plant growth regulators and could be useful for the development of new eco‐friendly herbicides. Objective: An NMR‐based metabolomics approach was reported to seek selective phytotoxic plant extracts and putative plant‐derived active molecules. Methods: Plant extracts derived from five Mediterranean donor species ( Pistacia lentiscus, Bellis sylvestris, Phleum subulatum, Petrohrhagia saxifraga and Melilotus neapolitana ) were used to treat the hydroponic cultures of three receiving plants ( Triticum durum, Triticum ovatum and Avena fatua ). Morphological analyses of the treated receiving plants were carried out. NMR‐based metabolomics was applied both to characterise the donor plant extracts and to study the effects of the treatments on the receiving plants. Results: This study allowed the identification of Melilotus neapolitana and Bellis sylvestris as phytotoxic plant and good candidates for further studies. Specifically, the NMR‐based metabolomics investigation showed that these species affect a specific set of metabolites (such as sugars, amino and organic acids) and therefore metabolic pathways [i.e. tricarboxylic acid (TCA) cycle, amino acid metabolism, etc.] that are crucial for the plant growth and development. Moreover, it was possible to identify the metabolite(s) probably responsible for the phytotoxicity of the active extracts. Conclusion: The NMR‐based metabolomics approach employed in this study led to the identification of two phytotoxic plant extracts and their putative active principles. These new insights will be of paramount importance in the future to find plant derived molecules endowed with phytotoxic activities. Abstract : Mediterranean plants are characterized by a high content of bioactive secondary metabolites that play important roles in plant‐plant interactions. Plant extracts derived from five Mediterranean donor species (Pistacia lentiscus, Bellis sylvestris, Phleum subulatum, Petrohrhagia saxifraga and Melilotus neapolitana) were used to treat the hydroponic cultures of three receiving plants (Triticum durum, Triticum ovatum and Avena fatua). The NMR‐based metabolomics approach employed in this study led to the identification of two phytotoxic plant extracts and their putative active principles.